Temperature effect on polymerization kinetics of poly methyl methacrylate (PMMA) - Noor Hariah , Wahab (2013)
Polymerization is a process which is chemically combined of small molecules to produce a very large chain or network molecule, called a polymer. By the way, the small molecules may be alike, or they may represent of two, three, or more different compounds with different molecular weight. This research proposes is to study the effect of temperature on polymerization kinetics of methyl methacrylate (MMA). Thermal study on methyl methacrylate is important to explain the heat and mass transfer phenomena during polymerization reaction. The objective of this study is to determine the temperature effect on polymerization kinetics of methyl methacrylate (MMA) with initiator. Mass of methyl methacrylate as monomer will be fixed at 3miligrams and also mass of initiator which is azo-bisisobutyronitrile (AIBN) will constant at 2miligrams. These two components will put on the pan by micropipette. The pan will tightly seal and be put into the differential scanning calorimetry (DSC). Each of samples will run until five hours in different temperatures (35°C, 45°C, 55°C, 65°C and 75° C). Then the polymerization kinetics and heat released are analyzed using this differential scanning calorimetry (DSC). From the (DSC) the curves or data of temperature, time and heat released are obtained. From these result obtained, increasing the temperature will decrease the time of reaction taken. High temperature will increase the amount of heat low or heat release. As increase the temperature, the rate of reaction increase due to the increasing of collision frequency and produce more energy to start the reaction.